Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1097/jsm.0000000000000358
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Injections for Adhesive Capsulitis

Abstract: Corticosteroid injections for AC demonstrate short-term efficacy, but may not provide a long-term benefit. More high quality, prospective studies are needed to determine whether corticosteroid injections using ultrasound guidance significantly improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Glenohumeral corticosteroid injection is routinely performed to treat idiopathic adhesive capsulitis and has been shown to provide symptomatic relief by inhibiting inflammation and production of prostaglandin 9 . However, the therapeutic benefits of the injection are largely affected by injection accuracy 6, 7.…”
Section: Discussionmentioning
confidence: 99%
“…Glenohumeral corticosteroid injection is routinely performed to treat idiopathic adhesive capsulitis and has been shown to provide symptomatic relief by inhibiting inflammation and production of prostaglandin 9 . However, the therapeutic benefits of the injection are largely affected by injection accuracy 6, 7.…”
Section: Discussionmentioning
confidence: 99%
“…A landmark-guided injection was used initially because there is insufficient evidence to justify the increased cost and inconvenience associated with image-guided injections given the lack of clearly defined benefit in terms of increased accuracy. 1 , 20 , 21 , 25 , 40 , 43 , 46 If patients do not improve after a landmark-guided injection and supervised PT, then a second, fluoroscopically guided glenohumeral joint injection followed by additional supervised PT is administered. At this point in the algorithm, a fluoroscopically guided injection is used because it is unlikely to be less accurate than a landmark-guided injection 1 , 20 , 21 , 40 , 43 , 46 and because we believe it is important to exhaust nonoperative therapies before considering surgical intervention.…”
Section: Methodsmentioning
confidence: 99%
“… 7 , 45 The greatest improvement occurs following early treatment of this condition, which can hasten resolution of symptoms sooner than if the condition is not treated. 16 , 28 , 44 46 This condition is most frequently treated conservatively with a combination of anti-inflammatory medications, home exercises, physical therapy, 10 , 15 , 36 and glenohumeral intra-articular corticosteroids. 31 , 34 , 38 Operative treatment consisting of manipulation under anesthesia with or without arthroscopic capsular release may be considered if patients do not improve with nonoperative measures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have shown that image-guided intra-articular steroid injections provide significant short-term benefits with regard to pain, ROM, and shoulder function compared with physical therapy alone 13,14,15 . This short-term improvement is clinically relevant because pain reduction not only alleviates symptoms but allows patients to move faster in the stages of rehabilitation and thus return to their daily life activities more rapidly 13,14 .…”
Section: Corticosteroid Injectionsmentioning
confidence: 99%